Positive electrode material and lithium ion secondary battery

By using a variety of lithium alloys and positive electrode active materials in the positive electrode material of lithium ion secondary batteries and forming a composite body through annealing treatment, the lithium ion consumption problem caused by the SEI film is solved, and the capacity maintenance rate and cycle stability of the battery are significantly improved.

CN119786548APending Publication Date: 2025-04-08TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411281905.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-04
Filing Date
2024-09-13
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The SEI film formed by the lithium-ion secondary battery during the initial charging causes lithium ions to consume, thereby reducing the battery capacity, and repeated charging and discharging will further reduce the battery capacity.

Method used

A positive electrode material including a positive electrode active material and two or more lithium alloys is used, wherein the metal element in the lithium alloy has an alloying potential of 0.5V (vs.Li/Li+) or more, such as bismuth, tin and antimony, and a composite is formed by annealing to suppress the movement of metal ions.

Benefits of technology

Effectively suppress the initial reduction of battery capacity, and reduce the reduction of battery capacity during repeated charging and discharging, significantly improving the cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005041901300000101
    Figure BDA0005041901300000101
  • Figure BDA0005041901300000111
    Figure BDA0005041901300000111
Patent Text Reader

Abstract

The invention relates to a positive electrode material and a lithium ion secondary battery. The positive electrode material contains a positive electrode active material and two or more types of lithium alloys, each of which contains a metal element having an alloying potential with lithium of 0.5 V (vs. Li / Li +) or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode material and a lithium ion secondary battery. Background Art

[0002] In a lithium-ion secondary battery, a portion of lithium ions released from the positive electrode active material during initial charge reacts with the electrolyte on the surface of the negative electrode to form a film called SEI (Solid Electrolyte Interphase).

[0003] The consumption of lithium ions associated with the formation of SEI becomes the cause of the reduction in battery capacity, so it is hoped that it is as small as possible. A strategy for suppressing the consumption of lithium ions associated with the formation of SEI has been proposed. The strategy is, for example, to make the positive electrode contain a lithium alloy while containing a positive electrode active material, and to use the lithium ions released from the lithium alloy during the initial charge to replenish the amount of lithium ions consumed by the formation of SEI. For example, refer to Japanese Patent Publication No. 2021-520614. Summary of the invention

[0004] In the method of making the positive electrode contain a lithium alloy, metal ions derived from the lithium alloy that has lost lithium ions move to the negative electrode side and precipitate. This precipitate may become a resistance layer and cause a decrease in battery capacity.

[0005] The present invention provides a positive electrode material for manufacturing a lithium ion secondary battery that suppresses the reduction in initial battery capacity and also suppresses the reduction in battery capacity caused by repeated charge and discharge. In addition, the present invention provides a lithium ion secondary battery manufactured using the positive electrode material.

[0006] Means for solving the above-mentioned problems include the following embodiments.

[0007] 1. A positive electrode material comprising a positive electrode active material and two or more lithium alloys, wherein the two or more lithium alloys respectively comprise a positive electrode active material having an alloying potential with lithium of 0.5 V (vs. Li / Li + ) or above metal elements.

[0008] 2. The positive electrode material according to 1, wherein the metal element is selected from bismuth, tin and antimony.

[0009] 3. The positive electrode material according to 1 or 2, wherein at least two of the lithium alloys contain metal elements with different crystal orientations.

[0010] 4. The positive electrode material according to any one of 1 to 3, wherein at least a part of the positive electrode active material and at least a part of the lithium alloy form a composite.

[0011] 5. A lithium ion secondary battery comprising a positive electrode, wherein the positive electrode comprises: a positive electrode active material, and an alloying potential with lithium of 0.5 V (vs. Li / Li + ) or more than two metallic elements.

[0012] According to one embodiment of the present disclosure, a positive electrode material capable of manufacturing a lithium ion secondary battery that suppresses a decrease in initial battery capacity and a decrease in battery capacity due to repeated charge and discharge, and a lithium ion secondary battery manufactured using the positive electrode material can be provided. DETAILED DESCRIPTION

[0013] In the present disclosure, a numerical range specified by “A to B”, “between A and B”, “from A to B”, etc. means a range including a minimum value A and a maximum value B.

[0014] In the numerical ranges recorded in stages in the present disclosure, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of other numerical ranges recorded in stages. In the numerical ranges recorded in the present disclosure, the upper limit or lower limit recorded in a certain numerical range can be replaced by the value shown in the embodiments.

[0015] In the present disclosure, the term "step" refers not only to an independent step but also to a step that cannot be clearly distinguished from other steps as long as the intended purpose of the step is achieved.

[0016] In the present disclosure, a combination of two or more preferred aspects is a more preferred aspect.

[0017] In the present disclosure, when there are plural substances corresponding to each component, the amount of each component refers to the total amount of the plural substances unless otherwise specified.

[0018] Cathode Materials

[0019] The positive electrode material disclosed herein comprises a positive electrode active material and two or more lithium alloys, wherein the two or more lithium alloys respectively comprise a positive electrode active material and a positive electrode active material having an alloying potential with lithium of 0.5 V (vs. Li / Li + ) or more metal elements.

[0020] As shown in the examples described below, a secondary battery produced using the positive electrode material of the present disclosure suppresses a decrease in battery capacity due to repeated charge and discharge even if the positive electrode contains a lithium alloy.

[0021] The reason for this is that, for example, dendrites composed of two or more metal elements derived from a lithium alloy generated in the negative electrode are more likely to diffuse (spread out) in the growth direction than dendrites composed of a single metal element, and the growth rate of the dendrites is slower.

[0022] Suppressing the growth rate of dendrites is also effective in preventing dendrites from breaking through the separator and causing a short circuit.

[0023] Lithium Alloy

[0024] Lithium alloys contain lithium with an alloying potential of 0.5 V (vs. Li / Li + ) or above metal elements.

[0025] Since the metal elements contained in the lithium alloy have the above alloying potential, the reduced lithium ions released from the positive electrode active material and consumed by the formation of SEI during the initial charge of the battery are effectively replenished. As a result, the initial reduction in battery capacity is effectively suppressed.

[0026] The alloying potential with lithium is 0.5 V (vs. Li / Li + ) or more metal elements include bismuth, tin and antimony. The alloying potential of bismuth (Bi) is 0.81 to 0.83 V. The alloying potential of tin (Sn) is 0.57 to 0.66 V. The alloying potential of antimony (Sb) is 0.94 to 0.96 V.

[0027] As a combination of two or more lithium alloys contained in the positive electrode material, a combination of a lithium alloy containing Bi (hereinafter also referred to as Li-Bi alloy) and a lithium alloy containing Sb (hereinafter also referred to as Li-Sb alloy) can be listed. In addition, as a combination of two or more lithium alloys contained in the positive electrode material, a combination of a Li-Bi alloy and a lithium alloy containing Sn (hereinafter also referred to as Li-Sn alloy) can be listed. Furthermore, as a combination of two or more lithium alloys contained in the positive electrode material, a combination of a Li-Bi alloy, a Li-Sb alloy, and a Li-Sn alloy can be listed.

[0028] Specific examples of the Li-Bi alloy include Li3Bi.

[0029] Specific examples of the Li—Sb alloy include Li 3 Sb.

[0030] Specific examples of the Li—Sn alloy include LiSn.

[0031] The positive electrode material preferably contains at least one of a Li—Sb alloy or a Li—Sn alloy and a Li—Bi alloy as two or more lithium alloys, and more preferably contains at least a Li—Bi alloy and a Li—Sb alloy.

[0032] From the viewpoint of diffusing the growth direction of dendrites, lithium alloys containing metal elements having different crystal orientations may be combined.

[0033] The crystal orientation of Bi is trigonal, the crystal orientation of Sn is tetragonal (cubic), and the crystal orientation of Sb is trigonal.

[0034] From the viewpoint of fully supplementing the consumption of lithium ions associated with the formation of SEI, the total content of the two or more lithium alloys contained in the positive electrode material is preferably 1 mass part or more relative to 100 mass parts of the positive electrode active material. From the viewpoint of fully supplementing the consumption of lithium ions associated with the formation of SEI, the total content of the two or more lithium alloys contained in the positive electrode material is more preferably 2 mass parts or more. From the viewpoint of fully supplementing the consumption of lithium ions associated with the formation of SEI, the total content of the two or more lithium alloys contained in the positive electrode material is further preferably 5 mass parts or more.

[0035] From the viewpoint of ensuring sufficient energy density, the total content of the two or more lithium alloys contained in the positive electrode material is relative to 100 parts by mass of positive electrode active material, preferably less than 30 parts by mass. From the viewpoint of ensuring sufficient energy density, the total content of the two or more lithium alloys contained in the positive electrode material is more preferably less than 20 parts by mass, further preferably less than 10 parts by mass.

[0036] In terms of the ratio of each lithium alloy in the two or more lithium alloys, for example, the content of the lithium alloy with the smallest content in the entire lithium alloy is preferably 10% by mass or more. In terms of the ratio of each lithium alloy in the two or more lithium alloys, for example, the content of the lithium alloy with the smallest content in the entire lithium alloy is more preferably 15% by mass or more, and further preferably 20% by mass or more.

[0037] The lithium alloy may be in the form of particles. The volume average particle size of the lithium alloy in the form of particles is not particularly limited, and can be selected from a range of, for example, 1 μm to 50 μm.

[0038] In the present disclosure, the volume average particle size of particles is a value (D50) at which the cumulative volume in a volume-based particle size distribution measured by a laser diffraction / scattering method is 50%.

[0039] Positive active material

[0040] The positive electrode active material contained in the positive electrode material includes composite oxides of lithium and transition metals (hereinafter also referred to as lithium transition metal composite oxides). The transition metal includes Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, W, etc.

[0041] Examples of the lithium transition metal composite oxide include layered lithium transition metal composite oxides, spinel lithium transition metal composite oxides, and olivine lithium transition metal composite oxides.

[0042] Specific examples of layered lithium composite oxides include LiCoO2, LiNiO2, LiMnO2, LiNi a Co b Mn c O2(a+b+c=1), and LiNi a Co b Mn c M d O2. In LiNi a Co b Mn c M d In O2, a+b+c+d=1 holds. In addition, in LiNi a Co b Mn c M d In O2, M is one or more additional elements selected from Al, Mg, La, Ti, Zn, B, W, Fe, Cr, V, Ru, Cu, Cd, Ag, Y, Sc, Ga, In, As, Sb, Pt, Au, Si, etc.

[0043] Specific examples of spinel-type lithium composite oxides include LiMn 2 O 4 .

[0044] Specific examples of the olivine-type lithium composite oxide include LiMPO 4 (M: Fe, Co, Ni, or Mn).

[0045] The positive electrode active material contained in the positive electrode material may be a single type or two or more types.

[0046] Among the lithium composite oxides, a lithium transition metal composite oxide containing at least one selected from Ni, Co and Mn as a transition metal is more preferred. In addition, among the lithium composite oxides, a lithium transition metal composite oxide containing Ni and at least one selected from Co and Mn as a transition metal is further preferred. Moreover, among the lithium composite oxides, a lithium transition metal composite oxide (NCM, nickel cobalt manganese oxide) containing Ni, Co and Mn as transition metals is further preferred.

[0047] Regarding the molar ratio of Ni, Co and Mn contained in the NCM, for example, the molar ratio of Ni to Co (Ni:Co) can be selected from the range of 1:0.1 to 1:1, and the molar ratio of Ni to Mn (Ni:Mn) can be selected from the range of 1:0.1 to 1:1.

[0048] The positive electrode active material may be in the form of particles.

[0049] The volume average particle size of the positive electrode active material in particulate form is not particularly limited, and can be selected from a range of 5 μm to 30 μm, for example. When the positive electrode active material is an aggregate of a plurality of primary particles, i.e., secondary particles, the volume average particle size is the volume average particle size of the secondary particles.

[0050] The positive electrode active material contained in the positive electrode material may be a single type or two or more types.

[0051] The volume average particle size of the positive electrode active material particles is not particularly limited, and can be selected from the range of 5 μm to 30 μm, for example.

[0052] Other Ingredients

[0053] The positive electrode material may be in the form of a mixture containing a positive electrode active material such as a conductive aid and a binder and components other than the lithium alloy. If necessary, a solvent may be added to the mixture to adjust the viscosity of the mixture.

[0054] Specific examples of the conductive auxiliary agent include carbon materials such as carbon black (acetylene black, thermal black, furnace black, etc.), carbon nanotubes, and graphite.

[0055] The conductive material contained in the positive electrode material may be a single type or two or more types.

[0056] Specific examples of the binder include polyvinylidene fluoride (PVDF), polyethylene, polypropylene, polyethylene terephthalate, cellulose, nitrocellulose, carboxymethyl cellulose, polyethylene oxide, polyepichlorohydrin, polyacrylonitrile, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), polyacrylate, and polymethacrylate.

[0057] The binder contained in the positive electrode material may be a single type or two or more types.

[0058] Method for manufacturing positive electrode material

[0059] From the viewpoint of suppressing the movement of metal ions from the lithium alloy contained in the positive electrode material to the negative electrode side, the method for manufacturing the positive electrode material preferably includes a step of heating the mixture of the positive electrode active material and two or more lithium alloys at a temperature of 350° C. or higher. Hereinafter, the step of heating the mixture of the positive electrode active material and two or more lithium alloys at a temperature of 350° C. or higher is also referred to as annealing treatment.

[0060] That is, one embodiment of the present disclosure is a method for producing a positive electrode material, comprising: obtaining a mixture including a positive electrode active material and two or more lithium alloys; and heating the mixture at a temperature of 350° C. or higher.

[0061] A secondary battery manufactured using a positive electrode material obtained by annealing a mixture of a positive electrode active material and two or more lithium alloys maintains the battery capacity well compared to a secondary battery manufactured using a positive electrode material obtained by annealing the mixture. The results are shown in the embodiments described below. As the main reason, it is believed that by annealing the mixture, solid solution diffusion of the positive electrode active material and the lithium alloy occurs to form a composite. It is believed that by becoming a state in which the lithium alloy is received in the composite, the movement of metal ions from the lithium alloy to the negative electrode side is suppressed.

[0062] The temperature of the annealing treatment is not particularly limited as long as it is 350° C. or higher, and may be 450° C. or higher, 550° C. or higher, or 650° C. or higher.

[0063] The temperature of the annealing treatment may be 1000° C. or lower, 900° C. or lower, or 800° C. or lower.

[0064] The annealing time is not particularly limited and can be selected from 30 minutes to 5 hours.

[0065] The annealing treatment is preferably performed in an inert atmosphere such as nitrogen or argon.

[0066] The mixture after the annealing treatment is preferably in a state where at least a part of the positive electrode active material and at least a part of the lithium alloy form a complex (solid solution, etc.).

[0067] The mixture after the annealing treatment may be crushed into particles.

[0068] The volume average particle size of the particles obtained by crushing the mixture after the annealing treatment can be selected from the range of 5 μm to 30 μm, for example.

[0069] The mixture after annealing treatment may be further mixed with components such as a conductive auxiliary agent and a binder.

[0070] positive electrode

[0071] The positive electrode material of the present disclosure can be used as a material for a positive electrode of a lithium ion secondary battery. The positive electrode includes, for example, a current collector and a positive electrode layer disposed on the current collector, and the positive electrode layer contains the positive electrode material of the present disclosure.

[0072] The positive electrode layer may be disposed on one surface of the current collector or on both surfaces of the current collector.

[0073] Examples of the material of the current collector constituting the positive electrode include aluminum, aluminum alloys, nickel, titanium, stainless steel, etc. Examples of the shape of the current collector include foil, mesh, and the like.

[0074] The positive electrode layer is disposed on the current collector, for example, by applying a slurry of positive electrode material to one or both sides of the current collector. If necessary, a pressurization treatment for adjusting the density of the positive electrode layer may be performed. There is no particular limitation on the thickness of the positive electrode layer, and for example, it can be selected from a range of 10 μm to 100 μm.

[0075] Lithium-ion secondary battery

[0076] The lithium ion secondary battery of the present disclosure includes a positive electrode, wherein the positive electrode includes: a positive electrode active material, and a lithium alloying potential of 0.5V (vs. Li / Li + ) or more than two metallic elements.

[0077] The two or more metal elements contained in the positive electrode may be in the form of a single metal or in the form of a lithium alloy.

[0078] At least a part of the two or more metal elements contained in the positive electrode may be in a state of forming a complex together with the positive electrode active material.

[0079] The detailed information and preferred forms of the positive electrode active material and the two or more metal elements contained in the positive electrode are the same as those of the positive electrode active material and the two or more metal elements contained in the above-mentioned positive electrode material.

[0080] The positive electrode in the lithium ion secondary battery of the present disclosure can be obtained by using the above-mentioned positive electrode material of the present disclosure.

[0081] Whether the positive electrode of the lithium ion secondary battery is obtained using the positive electrode material of the present disclosure can be confirmed by, for example, removing the negative electrode from the lithium ion secondary battery after charge and discharge and checking whether precipitates of the metal element contained in the positive electrode material are present in the negative electrode.

[0082] When a precipitate derived from a metal element contained in the lithium alloy used in the positive electrode material of the present disclosure is present in the negative electrode, it can be determined that the positive electrode of the battery is obtained using the positive electrode material of the present disclosure.

[0083] The lithium ion secondary battery of the present disclosure includes, for example, a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte.

[0084] The negative electrode includes, for example, a current collector and a negative electrode layer disposed on the current collector and containing a negative electrode active material.

[0085] Examples of the negative electrode active material include carbon materials such as graphite, hard carbon, soft carbon, and activated carbon, silicon, metallic lithium, lithium alloys, and lithium titanate (LTO).

[0086] Examples of the material of the current collector constituting the negative electrode include copper, copper alloys, nickel, titanium, stainless steel, etc. Examples of the shape of the current collector of the negative electrode include foil, mesh, and the like.

[0087] Examples of the separator include nonwoven fabrics, cloths, and microporous films containing polyolefins such as polyethylene and polypropylene as a main component.

[0088] The electrolyte may be any of a liquid or a solid. As a liquid electrolyte (electrolyte), a product obtained by dissolving a known electrolyte such as LiPF6 in an organic solvent can be used without particular limitation. As a solid electrolyte, a known solid electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, etc. can be used without particular limitation.

[0089] The present disclosure will be described in more detail below using examples, but the present invention is not limited to these examples.

[0090] Preparation of evaluation batteries

[0091] In the production of the batteries of the respective examples, NCM (LiNi 0.8 Co 0.1 Mn 0.1 O2) and LiB3, Li3Sb and LiSn as lithium alloys.

[0092] The amount of each component was adjusted so that the total volume of the positive electrode active material and the lithium alloy would be equal in each example.

[0093] In Examples 1 to 3, the mixture of the positive electrode active material and the lithium alloy shown in Table 1 was annealed at 700° C. for 2 hours in a nitrogen atmosphere and then crushed to obtain composite particles of the positive electrode active material and the lithium alloy.

[0094] In Examples 4 and 5 and Comparative Examples 1 to 3, the mixtures of the positive electrode active material and the lithium alloy shown in Table 1 were not subjected to annealing treatment.

[0095] A mixture (93 g) of a positive electrode active material and a lithium alloy, carbon black (4 g) as a conductive aid, PVDF (3 g) as a binder, and a solvent (NMP) were mixed to obtain a slurry-like positive electrode material. The obtained positive electrode material was applied to an aluminum foil and dried to obtain a positive electrode.

[0096] A laminated evaluation battery was prepared using an electrode body in which the obtained positive electrode, a separator (polyethylene microporous membrane), and a negative electrode containing graphite as an active material were stacked in sequence, and an electrolyte solution was a mixed solvent of ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate containing LiPF6 as an electrolyte.

[0097] Evaluation of battery performance

[0098] Based on the mass of the positive electrode active material contained in the battery, a current value of 210 mA / g was defined as 1C rate, and CCCV charge and CCCV discharge were performed under the following conditions. The obtained CCCV capacity was defined as the capacity of the battery (initial discharge capacity).

[0099] Lower voltage limit: 2.5V

[0100] Upper voltage limit: 4.25V

[0101] Charge and discharge current value: 0.2C

[0102] Termination current value: 0.03C

[0103] Then, a cycle test (CC charge and CC discharge) of the battery was carried out. Table 1 shows the number of cycles when the CC discharge capacity of the battery reached 40% or less of the initial discharge capacity.

[0104] As the number of cycles shown in Table 1 increases, it can be judged that the decrease in battery capacity due to repeated charge and discharge is suppressed.

[0105] Table 1

[0106]

[0107] As shown in Table 1, the batteries of Examples 1 to 5 using two lithium alloys as the positive electrode material showed a more excellent capacity retention rate than the batteries of Comparative Examples 1 to 3 using one lithium alloy as the positive electrode material.

[0108] Among Examples 1 to 5, Examples 1 to 3 in which the mixture of the positive electrode active material and the lithium alloy was annealed showed a more excellent capacity retention rate than Examples 4 and 5 in which the mixture of the positive electrode active material and the lithium alloy was not annealed.

[0109] Among Examples 1 to 3, the battery of Example 1 using a lithium alloy containing Bi and a lithium alloy containing Sb showed particularly excellent capacity retention. The reason for this is that, for example, the combination of Bi and Sb showed a topological insulator-like behavior, suppressing the ionization of the bulk.

[0110] Evaluation of the Release of Metal Ions from Lithium Alloys

[0111] After the cycle test, the battery (cell) was disassembled and the positive electrode was taken out. A sample solution was prepared from the positive electrode layer using an acid, and elemental analysis was performed using ICP-AES (ICP atomic emission spectroscopy).

[0112] The concentrations of the metal elements in the lithium alloy used for preparing the positive electrode are shown in Table 2 as ratios when the initial concentration is set to 100.

[0113] Table 2

[0114]

[0115] As shown in Table 2, the residual rate of the metal element derived from the lithium alloy in the positive electrode is higher in Examples 1 to 3 than in Examples 4 and 5 and Comparative Examples 1 to 3. In Examples 1 to 3, the mixture of the positive electrode active material and the lithium alloy was annealed. In Examples 4 and 5 and Comparative Examples 1 to 3, the mixture of the positive electrode active material and the lithium alloy was not annealed.

[0116] The above results suggest that the migration of metal elements from the lithium alloy to the negative electrode side is effectively suppressed by annealing the mixture of the positive electrode active material and the lithium alloy.

Claims

1. A positive electrode material comprising a positive electrode active material and two or more lithium alloys, The two or more lithium alloys respectively include a lithium alloy having an alloying potential of 0.5 V (vs. Li / Li + ) or more metal elements.

2. The positive electrode material according to claim 1, wherein The metal element is selected from bismuth, tin and antimony.

3. The positive electrode material according to claim 1, wherein At least two of the lithium alloys respectively contain metal elements with different crystal orientations.

4. The positive electrode material according to claim 1, wherein At least a portion of the positive electrode active material and at least a portion of the lithium alloy form a composite.

5. A lithium ion secondary battery comprising a positive electrode, The positive electrode comprises: a positive electrode active material and a lithium alloying potential of 0.5 V (vs. Li / Li + ) or more than two metallic elements.

Citation Information

Patent Citations

  • Positive electrode for secondary battery, method for producing same, and lithium secondary battery including same

    JP2021520614A